Provisions of Periods in the Matters of Personal Status and the Extent of the Judge's Power to Amend Them “Comparative Study” - علي, حميد سلطان; حسن, بان بدر (Journal of Legal Sciences, 2019)
Most modern legislations seeks to regulate the provisions that guarantee the stability of marital life, and that the Iraqi legislator along the lines of such legislation has ensured the stability of married life, therefore, he started to regulate the matters related to it, and in order to achieve these issues and the desired objectives, he adhered to limit these issues to periods that the parties must take into consideration when exercising these rights because they have serious effects that may lead to loss of these rights if they are not observed . In addition, the periods of personal status issues are divided into the considerations to several divisions included the related to their impact in terms of being constructing of the rights or subtracting to them including their source in terms of the legislator's intervention in their evaluation or granting their discretion to the judge. It is clear from the research that the determination of the durations in matters of civil status taking by the legislator and must be respected and the judge must abide by them in order to maintain the stability of the legal system. At the same time, however, the judge is granted the authority to modify the periods by increasing or decreasing or by specifying periods not specified by the law if the interests of the litigants are required or there are reasons to do so.